Corporate Social Responsibility, Good Corporate Governance, Environmental Performance And Firm Value - Leny Suzan; Pungki Atma Negara (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The purpose of carrying out this research is to determine the effect of CSR, GCG and EP on the value of companies included in the property and real estate sectors listed on the IDX from 2017 to 2021. The population in the study was 81 companies, and the methods purposive sampling was used to select a sample of 44 companies, resulting in total of 220 observational data. In analyzing the data, panel data regression was processed with the help of Eviews version 12. The results of this study show that environmental performance has an influence on the value of companies. The regression model shows a positive and statistically significant correlation between environmental performance and company value, then CSR and GCG do not affect company value